147k views
1 vote
Let f(x) = -3x^2 + 6x. Find f(2).

User ThorstenC
by
5.5k points

2 Answers

4 votes

Answer:

The correct answer is 0

Hope it helps

Explanation:

F(x) is given

So to find f2 we substitute all the variables (x) with the number 2 so it becomes..

f(2)=

-3(2)^2 + 6(2)

= -3(4)+ 6(2)

= -12+12

= 0

User Huntharo
by
5.7k points
5 votes

Answer:

0

Explanation:

Substitute x for 2

-3(2)^2 + 6(2)

Order of operations says that exponents are next, so square the 2

-3(4) + 6(2)

multiply

-12 + 12

add

0

User Max Zuber
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.